Deforestation and Violations Against Indigenous People’s Spiritual Rights in Indonesia: an Ecological Perspective - Ricco Andreas; Mona Ervita (Pancasila and Law Review, 2026)
This article examines the impact of deforestation on the spiritual rights of indigenous peoples in Indonesia through the lens of ecological justice. As one of the world's most biodiverse countries, Indonesia continues to experience deforestation driven by plantation expansion, mining activities, and infrastructure development. These processes have not only degraded forest ecosystems but have also disrupted the spiritual, cultural, and social relationships between indigenous communities and their customary territories. This study addresses two questions: (1) how deforestation affects indigenous peoples within the ecological justice framework, and (2) how state policies protect indigenous spiritual rights in the context of environmental governance. Using a normative legal method, this article analyzes constitutional provisions, environmental legislation, human rights instruments, and legal frameworks concerning indigenous peoples, supported by case studies of the Mutis Indigenous People in East Nusa Tenggara and the Suku Anak Dalam in Jambi. The findings indicate that development policies in Indonesia remain largely oriented toward economic growth and have not adequately integrated the protection of indigenous spiritual rights. Consequently, deforestation continues to threaten sacred sites, customary territories, cultural identity, and traditional livelihoods. This article argues that ecological justice provides an appropriate framework for balancing development, environmental protection, and indigenous rights through the recognition of customary territories, meaningful participation based on Free, Prior, and Informed Consent (FPIC), ecosystem protection, and intergenerational sustainability. The study contributes to the development of environmental law scholarship by positioning indigenous spiritual rights as an integral component of environmental governance and sustainable development in Indonesia.